2020
DOI: 10.1002/slct.202002515
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of a ZnO Nanolayer on TiO2 Nanorods Nanoarrays with Tailored Thickness towards Boosted Photoelectrochemical Hydrogen Production Activity

Abstract: In this study, one‐dimensional (1D) core‐shell structured TiO2@ZnO nanorod arrays have been synthesised by means of a simple hydrothermal method combining with subsequently ZnO atomic layer deposition (ALD). It was found that the thickness of the ZnO shell layers can be finely controlled with 20 nm, 30 nm, 40 nm and 50 nm by simply varying the deposition times. Photoelectrochemical (PEC) water splitting tests demonstrate that the TiO2@ZnO samples with 30 nm of ZnO layer yielded the highest photocurrent density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…[26] The type-II heterojunction semiconductors with narrow bandgap and matching energy level constructed on the surface of ZnO have attracted extensive attention, and are further developed into ternary type-II heterojunction semiconductors in subsequent research. [27][28][29][30][31][32] For example, Zhou et al constructed a ZnO/TiO 2 heterojunction semiconductor with a bird's nest-like structure, and its photocurrent density reached 2.75 mA/cm 2 at 1.23 V RHE , which was 2.27 times that of pure TiO 2 . [33] This study found that the bird's nest-like three-dimensional structure increased the contact area between the photoelectrode and sunlight, and the Z-type band-matching structure effectively inhibited the recombination of photogenerated holes and electrons at the interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26] The type-II heterojunction semiconductors with narrow bandgap and matching energy level constructed on the surface of ZnO have attracted extensive attention, and are further developed into ternary type-II heterojunction semiconductors in subsequent research. [27][28][29][30][31][32] For example, Zhou et al constructed a ZnO/TiO 2 heterojunction semiconductor with a bird's nest-like structure, and its photocurrent density reached 2.75 mA/cm 2 at 1.23 V RHE , which was 2.27 times that of pure TiO 2 . [33] This study found that the bird's nest-like three-dimensional structure increased the contact area between the photoelectrode and sunlight, and the Z-type band-matching structure effectively inhibited the recombination of photogenerated holes and electrons at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…prepared Y‐doped ZnO nanorod arrays using yttrium nitrate as the Y source, and found the introduction of Y 3+ effectively reduced the transmission resistance and improved the electric conductivity [26] . The type‐II heterojunction semiconductors with narrow bandgap and matching energy level constructed on the surface of ZnO have attracted extensive attention, and are further developed into ternary type‐II heterojunction semiconductors in subsequent research [27–32] . For example, Zhou et al.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the shortage of traditional energy, using solar energy photocatalysis to split water to evolve H 2 is an effective solution to solve the energy shortages. [1] At present, a variety of semiconductor photocatalysts with excellent performance have been prepared. [2][3][4][5][6] Metal-organic frameworks (MOFs) have been extensively studied because they have large specific surface area, tunable structure and high porosity.…”
Section: Introductionmentioning
confidence: 99%